THE ROLE OF CIVIC EDUCATION TEACHER’S PERCEPTION TO THE DEVELOPMENT OF LIFE SKILL STUDENTS OF SMP NEGERI I PULAU MOROTAI - Subhan Hayun (Peneliti.net, 2019)
This research discussed about the role of teachers Civic Education competence toward development of students life skills at SMP Negeri I Pulau Morotai. There are many ways can be applyied to increase the quality of education, one of them is development of students life skills based on the students field. To enhance Human resourch takes a long time and it must be supported by toughtful thinking, working hard and must be support by adequate facilities and infrastructures. Based on the problems above, aims of this research includes: 1) To know the ability of teachers in guiding the students, 2. To know the role of teacher to increase the students life skill at SMP I Morotai. To collect the data in this research through observation, interview and documentation. Technique to analyze the data by using qualitative descriptive. The result of this research shown that the teachers of Civic education at SMP Negeri I Pulau Morotai did learning prosess based on the criteria. Whereas the teachers prepare lesson plan, delivered the materials sistematically, care the students activity in the classroom, evaluating the materials in the last meeting dan scoring by using oral tes.